HRM and Marketing: Identifying the Impacts of Rapid Technological Advancements - Yusriani, Sri; Kamal, Nur Mustofa; Utomo, Kabul Wahyu; Rekarti, Endi; Patiro, Shine Pintor Siolemba (Dinasti Publisher, 2025)
The rapid evolution of technology has transformed various sectors, including Human Resource Management (HRM) and consumer services. This literature review, based on highly cited works in Google Scholar, investigates the significant variables influenced by the proliferation of digital applications in these fields. Key findings indicate that technological integration affects variables such as consumer trust, satisfaction, engagement, and loyalty, which are essential to both HRM and marketing strategies. The analysis also highlights the dual role of technology as both an enabler and a potential disruptor, depending on strategic implementation. This study provides a comprehensive basis for future research on leveraging technology for sustainable growth and improved management quality in HRM and marketing. Keyword: Technological advancements, HRM, consumer services, trust, engagement, loyalty, marketing strategies.